Platelet surface expression of cyclophilin A is associated with increased mortality in patients with symptomatic coronary artery disease - Rath, Dominik; Von Ungern-Sternberg, Saskia; Heinzmann, David; Sigle, Manuel; Monzien, Mona; Horstmann, Katja; Schaeffeler, Elke; Winter, Stefan; Mueller, Karin; Groga-Bada, Patrick; Zdanyte, Monika; Borst, Oliver; et al. (Journal of Thrombosis and Haemostasis, 2020)
Background: Cyclophilin A (CyPA) is an important intracellular molecule mediating essential cellular functions such as signaling and protein folding. Enhanced CyPA platelet surface expression is associated with hypertension and hypercholesterolemia in patients with stable coronary artery disease (CAD). In patients with acute myocardial infarction CyPA platelet surface expression is significantly decreased. The aim of this study was to investigate possible associations of CyPA platelet surface expression and a clinically relevant CyPA single-nucleotide polymorphism (CyPA PPIA rs6850) with prognosis in patients with symptomatic cardiovascular disease. Materials and methods: Blood was obtained from 335 consecutive patients with symptomatic CAD. All patients were followed up for 1080 days for endpoints all-cause death, myocardial infarction (MI), ischemic stroke, and bleeding. The primary combined endpoint was defined as a composite of all-cause death and/or MI and/or ischemic stroke. Cyclophilin A platelet surface expression levels less than or equal to the median were significantly associated with a worse prognosis (combined endpoint and all-cause death) when compared to CyPA greater than the median. Genotyping for CyPA PPIA rs6850 was performed in 752 patients with symptomatic CAD. Homozygous carriers of the minor allele showed a significantly worse cumulative event-free survival for both combined endpoint and MI when compared to carriers of the major allele. Conclusion: The CyPA platelet surface expression is associated with mortality whereas CyPA PPIA rs6850 is associated with recurrent MI in patients with symptomatic CAD. Cyclophilin A might offer a new biomarker for risk stratification and tailoring therapies in patients with cardiovascular disease.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Biomarkers; blood platelets; coronary artery disease; cyclophilin A; prognosis